Planting the seeds of polarization: Sharecropping, agrarian conflict and enduring political divides - Paolo Buonanno; Giacomo Plevani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2025)
This paper shows how enduring agrarian institutions shaped the long-run political consequences of historical shocks. We study Italy's sharecropping system (mezzadria)-a centuries-old fifty-fifty contract that structured rural relations across central Italy-and link its prewar prevalence to Socialist and Communist voting from 1913 to 1948. Using harmonized data for 720 agrarian zones and a combination of cross-sectional, entropy-balanced, and spatial RDD designs, we find that sharecropping was politically neutral before World War I but became a center of rural unrest and Fascist repression afterward. Areas with more sharecroppers experienced greater strike activity, targeted violence, and enduring left alignment. A daily panel of 1921 events shows repression peaking during annual contract renewals. The results reveal a "revolt-repression-realignment" mechanism through which local economic institutions converted wartime shocks into lasting partisan divides.
Keywords: P16; N54; N44; D72; D74; Q15; 330; sharecropping; agrarian conflict; repression; political polarization